Chinese anticipate their country’s future to be as bright as their personal future - Wang, Qi; Mert, Nazike; Cao, Yi; Hou, Yubo (Frontiers in Psychology, 2026)
Studies on future thinking in primarily Western populations have generally revealed a positivity bias toward the personal future and a negativity bias toward the nation’s future. The present research examined future thinking among Chinese, where college students (Study 1) and community adults (Study 2) were randomly assigned to a personal or a national future condition, where they imagined specific future events that might happen to them or their country in 1 week, 1 year, and 10–15 years. Participants rated the emotional valence and perceived control of each event and completed a wellbeing measure. As expected, Chinese participants imagined personal and national events similarly positive across all time points and perceived similar levels of control for the events. The positivity of personal future events and distant national future events was associated with psychological wellbeing. These findings shed new light on the anticipatory processes in personal and collective future thinking.